Daring to dream of an end to exile in sub-Saharan Africa - Marjon Kamara (Forced Migration Review, 2009)
Almost 98% of the refugees in Africa today could beconsidered as in protracted refugee situations. We needconcerted efforts to draw as many as possible to a close.